Clonagem e Expressão da Proteína gp19 de Ehrlichia canis - Brum, Fernanda Antunes (2010)
The Ehrlichia canis is a canine monocytic ehrlichiosis responsible for (EMC). The incubation period of EMC is 8 to 20 days, the disease has three phases: acute, subclinical and chronic. The species E. canis is transmitted to the dog and the man by the tick Rhipicephalus sanguineus. It is diagnosed by blood smear, serological or polymerase chain reaction (PCR), with the immunofluorescence method used. Recently E. canis was described as being capable of causing severe disease in humans, with death cases, mainly children and elderly. The gp 19 protein is an important immunodominant antigen, it induces rapid immune response in dogs. The similarity between the geographically distinct samples suggests that the gp19 protein can be used for testing the diagnostic immunoassays, as well as vaccination programs, because this protein is specific for E. canis and thus not have cross reactions with other genera of Ehrlichia.Este study aimed to clone and express the glycoprotein 19 of Ehrlichia canis in Escherichia coli for use as immunobiological, rapid and accurate detection of this disease. The gp 19 gene was amplified by polymerase chain reaction (PCR) using specific primers containing sites for restriction enzymes. The PCR product after digestion, was purified and cloned into a vector and inserted into E. pAE coli TOP 10 competent by electroporation. Of the identified clones was extracted plasmid, which was digested with restriction enzymes to confirm the presence of the insert. After selection of recombinant clones containing the gene linked to the vector, this was purified by heat shock and inserted in expression strain E. coli Star, cultured and induced to express the protein gp19.